Assessing Digital Readiness of Indonesian Hajj Pilgrims for Mobile Translation Tools - Aris Rakhmadi; Susilo Hartono (JURPIKAT, 2026)
The Hajj pilgrimage takes place in a multilingual environment that requires adequate communication skills from pilgrims. Indonesian Hajj pilgrims, particularly middle-aged and elderly individuals, often face language barriers when interacting with service providers and local communities. This community service activity aimed to assess pilgrims’ digital readiness as a foundational step toward the use of technology-based communication support. Conducted in collaboration with KBIHU Ahmad Dahlan Pringsewu, Lampung, the activity involved socialization sessions, hands-on assistance, and questionnaire-based feedback from 46 Hajj pilgrims. The findings indicate that 97.8% of participants reported sufficient to excellent smartphone literacy, reflecting a strong baseline of digital readiness. Nevertheless, communication support remains an unmet need, as 69.6% of participants preferred offline-capable application features. These results suggest that mobile translation tools, such as Google Translate, have strong potential as practical communication aids during Hajj. A follow-up community service program focused on hands-on training in the use of mobile translation tools is therefore recommended.